2013
DOI: 10.1128/mbio.00055-13
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing of the Plant Pathogen Taphrina deformans , the Causal Agent of Peach Leaf Curl

Abstract: Taphrina deformans is a fungus responsible for peach leaf curl, an important plant disease. It is phylogenetically assigned to the Taphrinomycotina subphylum, which includes the fission yeast and the mammalian pathogens of the genus Pneumocystis. We describe here the genome of T. deformans in the light of its dual plant-saprophytic/plant-parasitic lifestyle. The 13.3-Mb genome contains few identifiable repeated elements (ca. 1.5%) and a relatively high GC content (49.5%). A total of 5,735 protein-coding genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 72 publications
10
86
0
Order By: Relevance
“…The mechanisms of host adaptation and speciation of pathogenic fungal genomes are diverse, including accumulation of DNA point mutations, chromosomal rearrangement, loss of heterozygosity, ploidy change, and horizontal gene and chromosome transfer (Raffaele and Kamoun, ; Moller and Stukenbrock, ; Ene et al ., ). Recently, the genome sequences of T. deformans and three other Taphrina species, T. wiesneri , T. flavorubra , and T. populina , have been reported (Cisse et al ., ; Tsai et al ., ). Comparative genomics of these Taphrina pathogens showed that species‐specific aneuploidy and clustered secreted proteins are involved in the host adaptation (Tsai et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…The mechanisms of host adaptation and speciation of pathogenic fungal genomes are diverse, including accumulation of DNA point mutations, chromosomal rearrangement, loss of heterozygosity, ploidy change, and horizontal gene and chromosome transfer (Raffaele and Kamoun, ; Moller and Stukenbrock, ; Ene et al ., ). Recently, the genome sequences of T. deformans and three other Taphrina species, T. wiesneri , T. flavorubra , and T. populina , have been reported (Cisse et al ., ; Tsai et al ., ). Comparative genomics of these Taphrina pathogens showed that species‐specific aneuploidy and clustered secreted proteins are involved in the host adaptation (Tsai et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…In the genome of Taphrina deformans are found genes, responsible for the biosynthesis of compounds, related to the pathogenesis -proteases, which allow the digestion of plant tissues; secondary metabolites, which facilitate the interactions of the fungal pathogen with the environment, including the host plant; and hormones which are responsible for the typical hypertrophy and hyperplasia symptoms (Cisse et al, 2013). Therefore, the structural changes in the affected leaves are related to this hormonal disbalance provoked by the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The genomes of some economically important Taphrina species have recently been sequenced and reveal insights into the genetics underlying differences in symptom production, virulence, and adaption to host environments (Cissé et al 2013, Tsai et al 2014. The identification of orthologs of plant genes involved in hormone biosynthesis is of particular interest, as the production of hormones by pathogenic Taphrina species likely contributes to the distinctive disease symptoms they cause (Perley & Stowe 1966, Yamada et al 1990).…”
Section: Tissue Enlargement and Proliferationmentioning
confidence: 99%